A phase I randomized trial to assess the effect on skin infiltrate thickness and tolerability of topical phosphodiesterase inhibitors in the treatment of psoriasis vulgaris using a modified psoriasis plaque test. (1st September 2016) - Snape, S.D.; Wigger‐Alberti, W.; Goehring, U.M.
Summary: Background: Oral phosphodiesterase (PDE)4 inhibitors have shown efficacy in chronic obstructive pulmonary disease and psoriasis. Objectives: To assess the effectiveness, local safety and tolerability, and systemic pharmacokinetics of two topical PDE4 inhibitors, roflumilast and TAK‐084, in plaque psoriasis. Methods: An intraindividual comparison of six topical products was made in 15 patients aged 18–65 years with stable chronic plaque psoriasis in an investigator‐blinded, within‐subject randomized study. The products evaluated were calcipotriol 0·005% cream; betamethasone valerate 0·1% (both in their marketed formulations); investigational cream formulations of roflumilast 0·5% and TAK‐084 0·5% and 5%; and a vehicle cream formulation as a control. Each treatment was applied daily to different test sites located on psoriasis plaques for 3 weeks. Results: The primary end point of (mean) change from baseline in skin infiltrate thickness after 3 weeks of treatment showed statistically significant improvements for all treatments: betamethasone valerate cream (−286·9 μm), the selective PDE4 inhibitors roflumilast 0·5% (−237·1 μm) and TAK‐084 (0·5% cream, −153·6 μm; 5% cream, −216·7 μm) and calcipotriol 0·005% (−187·7 μm) when compared with vehicle cream control (all P < 0·001). Both the TAK‐084 5% and roflumilast 0·5% formulations performed well overall compared with the potent corticosteroid, betamethasone, and were ranked better than the vitamin D analogue calcipotriol. All adverse events were mild or moderate and none was serious. Conclusions: Topical treatment with cream formulations of the PDE4 inhibitors roflumilast and TAK‐084 reduced inflammation, measured as a change in skin infiltrate thickness, and reduced psoriasis severity. Corticosteroid treatments have known systemic and cutaneous side‐effects; PDE4 inhibitors could offer an alternative to these and deserve further study.